Chiral Separations in Normal‐phase Liquid Chromatography: Updating a Screening Strategy with a Chlorine‐containing Polysaccharide‐based Selector. Issue 12 (19th November 2015) - Zhou, Jie; Chen, Shanshan; Luo, Pei; Sun, Chong; Meng, Lingchang; Du, Qiuzheng; Sun, Fang
Abstract: The screening conditions of an existing column and mobile phase selection strategy for chiral compounds in normal‐phase high performance liquid chromatography (NP‐HPLC) were tested for their applicability on Chiralpak IC, which is a chiral stationary phase (CSP) made by immobilising cellulosic tris (3, 5‐dichlorophenyl‐carbamate) on silica gel. In this study, the applicability of the optimization steps of the existing separation strategy was examined using 36 compounds representing the three possible resolution situations that occur after screening. The cumulative number of separated compounds is 27 (75.0 %), and the cumulative number of baseline separated compounds is 19 (52.8 %). Abstract : The HPLC chromatograms of the compounds under the optimum chromatographic condition. Chromatographic conditions: labetalol: n‐hexane‐ethanol (95/5, V/V; 0.1DEA), the temperature was at 25 °C with a flow rate of 0.8 mL min −1 and the detection wavelength was set at 229 nm.